Macrophage‐derived extracellular vesicles mediate smooth muscle hyperplasia: role of altered miRNA cargo in response to HIV infection and substance abuse. Issue 9 (19th April 2018) - Sharma, Himanshu; Chinnappan, Mahendran; Agarwal, Stuti; Dalvi, Pranjali; Gunewardena, Sumedha; O'Brien-Ladner, Amy; Dhillon, Navneet K.
ABSTRACT: Our previous studies consistently demonstrate enhanced pulmonary vascular remodeling in HIV–infected intravenous drug users, and in simian immunodeficiency virus‐infected macaques or HIV‐transgenic rats exposed to opioids or cocaine. Although we reported an associated increase in perivascular inflammation, the exact role of inflammatory cells in the development of pulmonary vascular remodeling remains unknown. In this study, HIV–infected and cocaine (H+C)–treated human monocyte derived macrophages released a higher number of extracellular vesicles (EVs), compared to HIV‐infected or uninfected cocaine‐treated macrophages, with a significant increase in the particle size range to 100–150 nm. Treatment of primary human pulmonary arterial smooth muscle cells (HPASMCs) with these EVs resulted in a significant increase in smooth muscle proliferation. We also observed a significant increase in the miRNA‐130a level in the EVs derived from H+C‐treated macrophages that corresponded with the decrease in the expression of phosphatase and tensin homolog and tuberous sclerosis 1 and 2 and activation of PI3K/protein kinase B signaling in HPASMCs on addition of these EVs. Transfection of HPASMCs with antagomir‐130a–ameliorated the EV‐induced effect. Thus, we conclude that EVs derived from H+C‐treated macrophages promote pulmonary smooth muscle proliferation by delivery of its prosurvival miRNA cargo, which may play a crucial role in the development of PAH.—Sharma, H., Chinnappan, M., Agarwal, S., Dalvi, P., Gunewardena, S., O'Brien‐Ladner, A., Dhillon, N. K. Macrophage‐derived extracellular vesicles mediate smooth muscle hyperplasia: role of altered miRNA cargo in response to HIV infection and substance abuse. FASEBJ. 32, 5174–5185 (2018). www.fasebj.org